Integrated Model of Traceability - Jovana Zoroja; Mirjana Pejić Bach; Dubravka Omejec (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
In last few years, the problem of food safety is becoming bigger while consumers' awareness regarding social responsibility in production, distribution and consumption of food is growing. The main goal for food enterprises is to provide food traceability. This paper focus on traceability systems that can be used to attain the food safety through the systematic monitoring of physical movement of food related raw materials and finished products. In this paper, integrated model of traceability, based on three layers is presented. Our intention is to present concept of traceability which enterprises can use to ensure food safety and food tracking, while traceability concept refers to timely monitoring and accurate recording of product modification process through time and space.
Keywords: L67; M11; O14; 330; traceability; legal framework; quality management; supply chain; ICT